Fungi in association with chronic bacterial rhinosinusitis; relationship with a synergistic effect: a prospective study - Singh, Namit Kant; Garg, Lakshmi Narayan; Shekhar, Shubhranshu; Rao, Naiya; Kour, Chandpreet; Singh, Anshul; Kuhar, Hitesh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: The role of fungi as an etiological factor in the causation of chronic rhinosinusitis remains uncertain. The interaction of Fungi with bacteria can result formation of mixed biofilm which provide symbiotic relationship along with resistance from antimicrobials with an increased severity of symptoms. Methods: The cases of chronic rhinosinusitis were diagnosed and the grading of the symptom severity was done by visual analog scale in which symptoms of nasal blockage, rhinorrhea or post nasal drip, facial pain/headache, loss of smell, sleep disturbance/ fatigue were taken into consideration and each of the symptoms was graded from 1 to 10. Results: A strong association was detected between bacteria and fungi as 37 out of 40 (92.5%) amongst cases and 31 out of 40 (77.5%) amongst controls showed growth of both the organisms. Cases who were detected of having Fungi with Bacteria were having an average score of 8.364 and cases with bacteria alone were having an average score of 6.36. taking into consideration the individual symptom score and analyzing the data, the comparison between cases having both bacteria and fungi and cases with bacteria alone was found to be statistically significant with a p one-tail= 0.010221 and p two-tail= 0.020442. Conclusions: In chronic rhinosinusitis there is a higher incidence of poly microbial infection, and bacteria along with fungi co-exist with a synergistic effect leading to a higher morbidity.